for, in Legal Protection for Investors in Crowdfunding Services Through Information Technology Offers (Equity Crowdfunding) - Novia Choirunnisa; Nahdlotul Fadilah (Hang Tuah Law Journal, 2020)
The readiness of the community in the era of information technology has opened up opportunities in online businesses such as equity crowdfunding, equity crowdfunding as an alternative capital is increasingly in demand, especially by novice businesses. The Financial Services Authority issues regulations regarding the Equity Crowdfunding transaction model by issuing the Financial Services Authority Regulation Number 37 / POJK.04 / 2018. This provides questions for the regulation of Equity Crowdfunding in Indonesian Capital Market Law. The writer in this study would like to examine and analyze the Equity Crowdfunding activities and legal protection for investors, because legal protection is a form of legal certainty. The research method used is a normative juridical types, the problem approach uses the legislation approach and the conceptual approach. The results show that equity crowd funding is a form of new innovation in funding sources. The service mechanism has many similarities with public offering activities in the capital market, only the implementation is simpler. Equity Crowdfunding legal protection for investors who have been registered in the provisions of Chapter 54 paragraph (2) POJK Number 37 / POJK.04 / 2018, providing the latest information is only placed on the organizer's website or website.